PERAN MODAL SOSIAL DALAM MEMPERKUAT STRATEGI BERTAHAN HIDUP PENAMBANG BATU - Ritami, Eci; Hartoyo, Hartoyo (Sosiologi: Jurnal Ilmiah Kajian Ilmu Sosial dan Budaya, 2016)
This study aims to determine the socio economic life in thevillage of stone miners Sepancar Kulon Lawang, to determine the social capital stoneminers,to learn survival strategies rockminers and to determine the role of social capital in strengthening the rock miners a survival strategy. This study is used qualitative descriptive method to use data collection techniques interview,observation and documentation. The results showed that the socio economic conditions in the rock miners views of education obtained by the miners rock only to elementary school and did not complete primary school (elementaryschool). Low education obtained rock miners resulted in little opportunity to obtain decent employment and income erned was lower.That lower conditions made rock miners to do a strategy for survival. The strategy are to seeking loans when facing economic hardship, looking for another job,putting basic needs, saving money and also their participation in making a living wife. While social capital contained in the life of rock miners include three elements of social networks, trust and norms. Social capital plays a role in survival strategies do rock miners. Strategy of looking for a loan can be done by rock miners for their willingness to help of the party providing the loan. It is because of the belief that form of mutual aid.Keywords:Â  Socio-economic conditions, survival strategies, social capital